2017
DOI: 10.4103/1008-682x.173933
|View full text |Cite
|
Sign up to set email alerts
|

Inverse correlation between reactive oxygen species in unwashed semen and sperm motion parameters as measured by a computer-assisted semen analyzer

Abstract: This study investigated the correlation between sperm motion parameters obtained by a computer-assisted semen analyzer and levels of reactive oxygen species in unwashed semen. In total, 847 patients, except for azoospermic patients were investigated. At the time of each patient's first consultation, semen parameters were measured using SMAS™ or CellSoft 3000™, and production of reactive oxygen species was measured using a computer-driven LKB Wallac Luminometer 1251 Analyzer. The patients were divided into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 26 publications
3
38
2
Order By: Relevance
“…The luminescence values of the samples with greater than the threshold level, converted to per 10 6 spermatozoa and logarithmically transformed, were negatively correlated with the semen motile parameters that were measured by the SMAS ™ , except the LIN. These results were similar to those of other reports on the correlation between ROS in semen and semen parameters …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The luminescence values of the samples with greater than the threshold level, converted to per 10 6 spermatozoa and logarithmically transformed, were negatively correlated with the semen motile parameters that were measured by the SMAS ™ , except the LIN. These results were similar to those of other reports on the correlation between ROS in semen and semen parameters …”
Section: Discussionsupporting
confidence: 93%
“…This finding could be because the dose of luminol (100 mmol L –1 , 40 μL) in the current study was higher than that in other reports . The authors assumed that increasing the dose of luminol would make ROS detection clearer and the authors adopted the luminol dose that was reported by a specific study . However, in this study's results, the percentage of the semen samples in Groups A and B were 31.9 and 14.1%, respectively.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations